2015
DOI: 10.4031/mtsj.49.4.9
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges and Opportunities of Using Data in Teaching From the Perspective of Undergraduate Oceanography Professors

Abstract: A B S T R A C TA community survey of undergraduate professors was conducted along with subsequent interviews of community college professors to gather information on the practices and teaching needs of members of the oceanographic community. Our objective was to capture how undergraduate professors are currently using oceanographic data in their teaching, to what degree they are using inquiry in their undergraduate teaching, and information on what effective practices exist for teaching with data. The majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In contrast to instructor-generated activities, the final project allowed for student-designed questions and procedures. This encouraged "open inquiry," an experience that is exceedingly rare in undergraduate oceanography teaching (McDonnell et al, 2015). In general, inquiry-based learning develops cognitive skills on higher levels of Bloom's taxonomy (Bloom et al, 1956;Krathwohl, 2002).…”
Section: Assignments and Final Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to instructor-generated activities, the final project allowed for student-designed questions and procedures. This encouraged "open inquiry," an experience that is exceedingly rare in undergraduate oceanography teaching (McDonnell et al, 2015). In general, inquiry-based learning develops cognitive skills on higher levels of Bloom's taxonomy (Bloom et al, 1956;Krathwohl, 2002).…”
Section: Assignments and Final Projectmentioning
confidence: 99%
“…Active modalities -including those designated as "high-impact educational practices" (Kuh et al, 2017) -stand in contrast to traditional lecturing, which represents about three-quarters of class time across STEM undergraduate and graduate courses today (Stains et al, 2018). In a survey of almost 200 undergraduate oceanography professors, for example, three-quarters indicated that they use data in their instruction but are most likely to teach using lectures, rather than creating opportunities for active inquiry (McDonnell et al, 2015). There is strong evidence that using active learning techniques increases students'…”
Section: Introductionmentioning
confidence: 99%
“…These professors also recommended that EPE develop tools for creating basic statistics (e.g., calculation of mean, standard deviation, standard error, correlation coefficient, regression line), interpolating data, and helping students visualize time-series data sets (McDonnell et al, 2015). The professors also supported the development of a specialized tool that would allow them to create lessons using OOI data, rate FIGURE 2.…”
Section: The Process: Building Epe Tools For Undergraduate Student Lementioning
confidence: 99%
“…Finally, undergraduate survey results demonstrate that they need more guidance and support to learn how to interpret graphs. Students found the graphs difficult to read and interpret (e.g., the axes were sometimes unclear; more captions, key terms, visualizations, videos, and maps were needed to understand data sources; photos of instruments were requested; McDonnell et al, 2015). Some key outcomes include:…”
Section: Implementing Epe Tools: How Can the Tools Be Used In Undergrmentioning
confidence: 99%
“…These data, made publicly available in real time, constitute a valuable resource that undergraduate educators can use to teach a range of oceanographic principles and make the scientific process tangible. Using real data in undergraduate science education offers significant benefits for developing students' analytical and problem-solving skills (e.g., Gougis et al, 2017;O'Reilly et al, 2017;McDonnell et al, 2015).…”
Section: Introductionmentioning
confidence: 99%